Impact of COVID‐19 on HIV late diagnosis in a specialized German centre. Issue 11 (20th October 2022) - van Bremen, Kathrin; Monin, Malte; Schlabe, Stefan; Bischoff, Jenny; Rieke, Gereon Jonas; Schwarze‐Zander, Carolynne; Wasmuth, Jan‐Christian; Rockstroh, Jürgen K.; Boesecke, Christoph
Abstract: Background: The ongoing COVID‐19 pandemic has been impeding HIV diagnosis and treatment worldwide. Data on the impact of COVID‐19 on late diagnosis (LD) in Germany are lacking. Here we present novel data of a single‐centre German HIV cohort assessing LD during COVID‐19. Methods: This is a non‐interventional, single‐centre retrospective cohort assessing the rate of LD comparing HIV diagnoses pre‐COVID‐19 with those during the COVID‐19 pandemic. New diagnoses between 1 January 2019 and 1 February 2020 were classified as pre‐COVID‐19, and diagnoses between 1 February 2020 and 1 October 2021 were classified as during COVID‐19. Results: Between 1 January 2019 and 1 October 2021, 75 patients presented with newly diagnosed HIV infection, 34 pre‐COVID‐19 and 41 during COVID‐19. LD increased to 83% ( n  = 34/41) during COVID‐19 versus 59% ( n  = 20/34) pre‐COVID‐19, and CDC stage C3 rose to 44% ( n  = 18) versus 27%. Hospitalization rate increased to 49% ( n  = 20) during COVID‐19 versus 29% pre‐COVID‐19, and 12% ( n  = 5) presented with HIV‐associated neurological disease, whereas none were observed in the pre‐COVID‐19 group. The incidence of LD ( p  = 0.020), CD4 count < 350 cells/μL ( p  = 0.037) and < 200 cells/μL ( p  = 0.022) were statistically significantly associated with the ongoing COVID‐pandemic. An association with HIV transmission risk was borderline significant ( p  = 0.055). Conclusions: Despite comparable annual rates of new HIV diagnoses, LD has been increasing during the COVID‐19 pandemic, resulting in more opportunistic infections and higher hospitalization rates, possibly reflecting pandemic‐related shortages in HIV testing and care facilities. Maintaining HIV testing opportunities and access to treatment during a pandemic is crucial so as not to impede WHO elimination goals and so as to prevent an increase in AIDS‐related morbidity and mortality.